A review of research on professional learning communities in mainland China (2006–2015): Key findings and emerging themes. (September 2018) - Qiao, Xuefeng; Yu, Shulin; Zhang, Limin
In the last decade, there has been growing interest in professional learning communities (PLCs) outside mainstream Western contexts. In this paper, we provide a narrative synthesis of empirical studies of PLCs in kindergarten to 12th grade educational systems in mainland China published between 2006 and 2015. The review reveals five major emerging themes in the published literature: PLC characteristics; PLC practices in different regions; teacher collaboration in PLCs; the roles of university researchers; and educational leadership in PLCs. Significant progress has been identified in the enhancement of social harmony in teaching research groups, structural teacher collaboration, the construction of transregional PLCs and the complex roles of university researchers and school leaders. However, compared with the literature on PLCs in Western contexts, research on these communities in mainland China is still far from mature. The authors highlight the need for more empirically solid research on the development of sustainable PLCs in mainland China.